PENGARUH KOMPETENSI, INTEGRITAS, OBJEKTIVITAS, INDEPENDENSI DAN SKEPTISME PROFESIONAL APARAT PENGAWAS INTERNAL PEMERINTAH (APIP) TERHADAP KUALITAS PEMERIKSAAN DI PROVINSI BENGKULU - Hendri; Willy ab; Praningrum (Universitas Bengkulu, 2022)
Abstract : This study aims to determine the effect of competence, integrity, objectivity, independence and professional skepticism of the Government Internal Supervisory Apparatus (GISA) on the Quality of Examination in Bengkulu Province. This type of research is quantitative with non-probability sampling method where the entire population is used as GISA in Bengkulu Province using multiple linear regression analysis. The results of this study are competence, integrity, objectivity, independence and professional skepticism proved to have a positive and significant influence on the quality of the examination either partially or simultaneously. This means that the quality of the examination will be influenced by competence in the form of knowledge, skills, motives, traits and self-concept, maintained GISA integrity, objectivity by acting professionally and avoiding conflicts of interest, independence both in practice and in the profession and promoting an attitude of professional skepticism. The results of this study are expected to be implemented and become an effective solution for regional heads, leaders of GISA and GISA themselves in order to increase GISA's knowledge in understanding technical supervision, improve traits and self-concept, increase adherence to the code of ethics, strengthen responsibility in giving opinions and eliminate concerns about threats and intimidation, increasing GISA's objectivity by maintaining a neutral attitude and strengthening GISAs so that they are not placed in positions that are contrary to their profession, increasing GISA's independence in providing opinions in a practical way, maintaining GISA's professional skepticism during the implementation of audit activities by not rushing to give a statement on the report presented by the auditee if the auditee has not provided sufficient evidence, guiding the conformity of the audit with the standard with the audit method that has been determined and increasing the accuracy of the report on the results of the audit by only present explanations of evidence findings that are contrary to the provisions so that the quality of the examination is getting better Keywords: Competence, Integrity, Professional Skepticism. Abstrak : Penelitian ini bertujuan untuk mengetahui pengaruh kompetensi, integritas, objektivitas, independensi dan skeptisisme profesional Aparatur Pengawasan Intern Pemerintah (APIP) terhadap Kualitas Pemeriksaan di Provinsi Bengkulu. Jenis penelitian ini adalah kuantitatif dengan metode non-probability sampling dimana seluruh APIP di Provinsi Bengkulu dijadikan sampel , alat analisis menggunakan analisis regresi linier berganda. Hasil penelitian ini adalah kompetensi, integritas, objektivitas, independensi dan skeptisisme profesional terbukti berpengaruh positif dan signifikan terhadap kualitas pemeriksaan baik secara parsial maupun simultan. Artinya kualitas pemeriksaan akan dipengaruhi oleh kompetensi berupa pengetahuan, keterampilan, motif, sifat dan konsep diri, integritas APIP yang terjaga, objektivitas dengan bertindak secara profesional dan menghindari benturan kepentingan, independensi baik dalam praktik maupun dalam praktik. profesi dan mempromosikan sikap skeptisisme profesional. Hasil penelitian ini diharapkan dapat di implementasikan dan menjadi solusi yang efektif bagi kepala daerah, pimpinan APIP dan APIP sendiri guna pemecahan masalah terkait kualitas pemeriksaan yang dilaksanakan oleh APIP dalam rangka mendukung pelaksanaan program pemeriksaan dan membuat suatu kebijakan diataranya: meningkatkan kompetensi APIP dalam memahami teknis pengawasan, meningkatkan integritas APIP dengan mentaati kode etik, meningkatkan objektivitas APIP dalam menjaga sikap netral serta penguatan APIP agar tidak ditempatkan pada posisi yang bertentangan dengan profesinya, meningkatkan independensi APIP dalam memberikan opini secara praktisi serta mempertahankan sikap skeptisme profesional APIP selama pelaksanaan kegiatan pemeriksaan dan meningkatkan akurasi laporan hasil pemeriksaan sehingga kualitas pemeriksaan APIP meningkat menjadi lebih baik. Kata kunci: Kompetensi, Integritas, Skeptisme profesional.